CNC robotics : build your own workshop bot - Williams, Geoff (New York: McGraw-Hill, 2003)
Provides step-by-step instructions for designing, constructing, and testing a fully functional CNC robot.
Includes index.
Keywords: Robotics -- Research -- Congresses; Machine-tools -- Numerical control -- Programming; Machine-tools -- Design and construction